(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background and Objectives Coronary artery disease is a significant global health problem and is a leading cause of disability and death. In this study, the effect of coronary artery bypass graft (CABG) surgery on left ventricular (LV) systolic functions and regional wall motion abnormalities preoperative and one year postoperative was evaluated through echocardiographic techniques. Methods This is a prospective observational cross-sectional descriptive study. Two hundred adult patients with proven coronary artery disease selected without gender discrimination underwent coronary artery bypass grafting surgery at Cardiothoracic Surgery Department, Kasr Al Ainy hospitals, Cairo University in the period from March 2021 to October 2021. Regional wall Motion score index (RWMSI) was used by echocardiography to note if segmental left ventricular wall motion at basal, mid and apical levels were normal, hypokinetic, akinetic, dyskinetic, or aneurysmal preoperative and one year post-operative. Results All patients had chest pain preoperatively, and most of them were in Canadian Cardiovascular Society (CCS) Class III and IV. All patients had multi vessel disease and the left anterior descending was the most common vessel affected, complete revascularization was done in all patients using 3 to 5 grafts and left internal mammary artery was used in all patients. There was significant improvement in LVEF that changed from (59.33 to 62.76) . There was also a significant improvement of WMSI that changed from (1.19 to 1.10) one year after surgery. Conclusion This study suggests that CABG has a positive effect on LV systolic functions and improvement of RWMSI one year post‑operatively as confirmed through echocardiographic techniques.